In the Blood of Our Brothers : Abolitionism and the End of the Slave Trade in Spain's Atlantic Empire, 1800-1870 - Sanjurjo, Jesús, 1991- (Book collections on Project MUSE., 2021)
"This book details the abolition of the slave trade in Spanish America to the 1860s"--